Nanodiamond‐Based Separators for Supercapacitors Realized on Paper Substrates. Issue 6 (31st March 2020) - Polino, Giuseppina; Scaramella, Alessandro; Manca, Valerio; Palmieri, Elena; Tamburri, Emanuela; Orlanducci, Silvia; Brunetti, Francesca
Abstract : In response to the request for sustainable high performance energy storage devices, a significant interest is focused on developing environmentally friendly supercapacitors. In this context, cellulose‐based substrates for energy storage devices can be well‐engineered, lightweight, safe, thin, and flexible. Herein, a scalable, low‐cost, and easy‐to‐process approach for the preparation of supercapacitors using large area techniques like spray and blade coating is presented. Following a green strategy, all components are chosen or formulated in water‐based dispersions. Symmetric supercapacitors using common copy paper and electronic paper as the substrate, and poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) as electrodes, are realized and investigated. The novelty of this work consists of the use of composites based on detonation nanodiamonds (DNDs) and hydroxypropyl cellulose (HPC) as a solid‐state electrolyte and separator. Devices with solution electrolyte using the same HPC + DND composite but with the addition of sodium sulfate are prepared. The performance obtained using solid electrolyte (HPC + DNDs) and liquid electrolyte (HPC + DNDs + Na2 SO4 ) on both substrates is comparable in terms of specific capacitance: ≈0.13 – 0.52 F g −1 for (HPC + DNDs) and ≈0.35 – 0.82 F g −1 for (HPC + DNDs + Na2 SO4 ), with power density in the range of ≈19 – 24 μW cm −2 . Abstract : A scalable, low‐cost, and easy‐to‐process approach for the preparation of symmetric paper‐based supercapacitors using spray and blade coating techniques is reported. Following a green strategy, all components are formulated in water‐based dispersions. The novelty of this work is the use of hydroxypropyl cellulose charged with detonation nanodiamonds and sodium sulfate to realize the separator and electrolyte.